THE ALIGNMENT BETWEEN SYSTEM AND OPERATIONAL EFFECTIVENESS: A CASE STUDY IN THE ELECTRICAL SECTOR IN AUSTRALIA. - Medina Aguirre, Francisco Alejandro; Knott, Andrew (Scientia et Technica, 2012)
Organizations are increasingly investing in complex enterprise information systems.  In most cases, claims are made concerning how these expensive systems will produce considerable improvements in the operational performance of the organizations.  Nevertheless, there is evidence that many of these systems fail to deliver the expected outcomes and often fail completely.  This study explores the linkages among system effectiveness, operational performance, and the organizational factors that influence the balance that these systems require. As current literature is silent in regard to such interactions, this research uses a qualitative approach, based on unstructured interviews with employees at different levels in an electricity distribution enterprise, to build on the existing literature and to further confirm and refine a theoretical framework.